PENGARUH SISTEM KERJA TERHADAP KINERJA PERGURUAN TINGGI DAN IMPLIKASINYA TERHADAP KEPERCAYAAN MAHASISWA UNIVERSITAS SYIAH KUALA BANDA ACEH - Afrida Yahya; Riski Amalia (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2016)
In Indonesia especially in Aceh Province, the public universities aremost prefered by students, because the public university has high quality and prestige compared to private university. However, recently some publicuniversities show low performance indicates by low accreditation grade. Thisstudy aim was to evaluate impact of the works system which is adopted by certain university on the key performance indicator of the university and to evaluate the influence of performance of the university on the student trust. This study was conducted in Syiah Kuala University, Banda Aceh. This university has grade C of national accreditation for 2009-2014 periode. This is the descriptive and verification studies where the survey method was used by using the questionnaire. The linear regression model was performanced to evaluate the effect of dependent variables on dependent variable. A total of 170 responds were involved in this study comprises of academic staffs, students, supporting staffs, parents of student.